Simulation of characteristic features of Asian summer monsoon using a regional climate model
Lkkj & bl ’kks/k&i= esa HkweaMyh; tyok;q ifjorZu ds ifj.kkeLo:i ’krkCnh ds e/; ¼2041&60½ ds nkSjku ,f’k;kbZ xzh"edkyhu ekulwu ds fof’k"V yk.kksa dk iwokZuqeku djus ds mÌs’; ls vuqdj.k iz;ksxksa ds ifj.kke izLrqr fd, x, gSaA blds fy, gSMys tyok;q iwokZuqeku vkSj vuqla/kku dsUnz] ;w- ds- dk ks=h; tyok;q ekWMy gSM vkj- ,e- 2 dk mi;ksx fd;k x;k gSA ,f’k;kbZ ks= ds fy, 20 o"kksZa dh vof/k ds nks vuqdj.k iz;ksx fd, x, gSa uker% igyk] 1990 Lrjksa ds vuq:i xzhu gkml xSl lkanz.k dh fu/kkZfjr ek=k] ftls dUVªksy ¼lh- Vh- ,y-½ iz;ksx dgk x;k gS vkSj nwljk 1990 ls ysdj 2041&60 rd ds fy, xzhu gkml xSl lkanz.k ds okf"kZd feJ.k esa 1 izfr’kr dh o`f) lesr ftls vkxs xzhu gkml xSl ¼th- ,p- th-½ iz;ksx dgk x;k gSA xzhu gkml xSl lkanz.k esa okf"kZd feJ.k esa 1 izfr’kr dh o`f) tyok;q ifjorZu ds var% ljdkjh iSuy vkbZ- ih- lh- lh- kjk rS;kj dh xbZ ;kstuk ls yh xbZ gSA bu iz;ksxksa ls ’krkCnh ds e/; ds nkSjku ,f’k;kbZ xzh"edkyhu ekulwu esa ik, tkus okys fof’k"V yk.kksa esa gksus okys dqN ifjorZuksa dk irk pyk gS ftudk c<+s gq, ekuotfur mRltZdksa ds dkj.k gksuk LokHkkfor gSA lewph ekulwu _rq ds nkSjku Hkkjrh; ks= ij fuEu kksHk eaMy ¼850 gSDVkikLdy½ esa ekulwu nzks.kh ¼,e- Vh- ½ dk mRrj dh vksj lkekU; :i ls c<+uk lcls vf/kd egRoiw.kZ ifjorZu izrhr gksrk gSA vuqdj.k ifj.kkeksa ls ekulwu _rq ds nkSjku vjc lkxj esa leqnz Lrj nkc ¼,l- ,y- ih-½ esa yxHkx 1&2 gS- ik- dh o`f) dk irk pyk gS ftlds ifj.kkeLo:i fuEu kksHk eaMy esa vlkekU; izfrpØokr gksrs gSaA bldk vFkZ ;g gqvk fd fuEu Lrjh; tsV ¼,y- ,y- ts-½ vkSj vjc lkxj esa ekulwu dh /kkjk det+ksj iM+ tkrh gSA ;g ekWMy m".krj leqnz lrg dh fLFkfr;ksa esa fgan egklkxj ds mRrj esa ekulwuh pØokrh; fokksHkksa dh vko`fr esa deh dks vuqdfjr djrk gS tks gky gh ds n’kdksa esa ekulwu ds vonkcksa dh vko`fr esa deh dh izo`fr;ksa ds vuq:i ikbZ xbZ gSA bu iz;ksxksa ls ;g irk pyrk gS fd ikfdLrku vkSj mlds lehiorhZ mRrjh if’peh Hkkjr ds Åij Å"ek fuEunkc rhoz gks ldrk gS vkSj ekulwu _rq ds nkSjku FkksM+k iwoZ dh vksj c<+ ldrh gSA ;g ekWMy] Hkkjrh; leqnz ds nfk.kh Hkkxksa esa 8° & 10° m- ds chp 100 gS- ik- ¼Vh- bZ- ts- dksj dk Lrj½ ij fo’ks"kdj ekulwu ds iwokZ)Z ds nkSjku m".kdfVca/kh; iwokZfHkeq[kh tsV¼Vh- bZ- ts-½ dks izHkkfor djrk gSA The paper presents the results of simulation experiments aimed at predicting the characteristic features of Asian Summer Monsoon during the middle of the century (2041-60) resulting from global climate change. The model used is HadRM2 regional climate model of the Hadley Centre for Climate Prediction and Research, UK. Two simulation experiments of 20 years length have been performed for the Asian domain, namely, one with a fixed amount of greenhouse gas concentration corresponding to 1990 levels called the ’control’ (CTL) experiment and the other with the annual compound increase of 1 % in the greenhouse gas concentration for 2041-60 from 1990 onwards called the ’greenhouse gas’ (GHG) experiment. The annual compound increment of 1 %, in the greenhouse gas concentration has been adopted from the projection given by the Intergovernmental Panel for Climate Change (IPCC). The experiments have brought out some of the changes in the characteristic features of mid-century Asian summer monsoons that are expected to occur due to increased anthropogenic emissions. The most significant change seems to be a general northward shift of the monsoon trough (MT) in the lower troposphere (850 hPa) throughout the monsoon season over the Indian region. The simulation results have shown an increase of about 1-2 hPa in the sea level pressure (SLP) over the Arabian Sea during the monsoon resulting in an anomalous anticyclone over there in the lower troposphere. This would mean the weakening of Low Level Jet (LLJ) and the Arabian sea branch of the monsoon current. The model has simulated a decrease in the frequency of the monsoonal cyclonic disturbances over the north Indian Ocean under the warmer sea surface conditions which conforms to the observed decreasing trends in the frequency of monsoon depressions in recent decades. The experiments have shown that the Heat Low over Pakistan and adjoining northwest India, may intensify and shift slightly eastward during the monsoon. The model has simulated the strengthening of Tropical Easterly Jet (TEJ) at 100 hPa (the location of TEJ core ) over the southern parts of Indian sea between 8° - 10° N, especially during the first half of the monsoon season. , number=2, journal=MAUSAM, author=SINGH, O. P. and KUMAR, K. RUPA and MISHRA, P. K. and KUMAR, K. KRISHNA and PATWARDHAN, S. K., year=2006, month=Apr., pages=221–230